2022
DOI: 10.3390/ijerph192114552
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Effectiveness of a Pharmacotherapeutic Follow-Up Service for People with Tuberculosis in Primary Healthcare

Abstract: Tuberculosis (TB) is a disease of great relevance, responsible for 1.5 million deaths worldwide. Therefore, actions to control TB are necessary, and pharmacists may play an important role, especially in primary healthcare (PHC), where the diagnosis and management of this infection occurs. In a large Brazilian city, pharmacotherapeutic follow-up in PHC has been offered by pharmacists to people with TB since 2018. The objective of this study was to evaluate the implementation and effectiveness of this service th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Thirteen articles were included in this review that reported data on 3,886 patients. Four studies were conducted in USA (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Tavitian et al, 2003 ), two studies in Brazil (Lara-Júnior et al, 2022 ; Lopes et al, 2017 ) and one study was conducted in each of the following countires: Spain (Juan et al, 2006 ), China (Tang et al, 2018 ), Turkey (Clark et al, 2007 ), Canada (Tang et al, 2018 ), Thailand (Tanvejsilp et al, 2017 ), Indonesia (Karuniawati et al, 2019 ), and India (Thomas et al, 2018 ). There were 10 cohort studies (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Juan et al, 2006 ; Lara-Júnior et al, 2022 ; Lopes et al, 2017 ; Moadebi et al, 2005 ; Tanvejsilp et al, 2017 ; Tavitian et al, 2003 ; Thomas et al, 2018 ), two RCTs (Clark et al, 2007 ; Tang et al, 2018 ) and 1 quasi-experimental study (Karuniawati et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen articles were included in this review that reported data on 3,886 patients. Four studies were conducted in USA (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Tavitian et al, 2003 ), two studies in Brazil (Lara-Júnior et al, 2022 ; Lopes et al, 2017 ) and one study was conducted in each of the following countires: Spain (Juan et al, 2006 ), China (Tang et al, 2018 ), Turkey (Clark et al, 2007 ), Canada (Tang et al, 2018 ), Thailand (Tanvejsilp et al, 2017 ), Indonesia (Karuniawati et al, 2019 ), and India (Thomas et al, 2018 ). There were 10 cohort studies (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Juan et al, 2006 ; Lara-Júnior et al, 2022 ; Lopes et al, 2017 ; Moadebi et al, 2005 ; Tanvejsilp et al, 2017 ; Tavitian et al, 2003 ; Thomas et al, 2018 ), two RCTs (Clark et al, 2007 ; Tang et al, 2018 ) and 1 quasi-experimental study (Karuniawati et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were conducted in USA (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Tavitian et al, 2003 ), two studies in Brazil (Lara-Júnior et al, 2022 ; Lopes et al, 2017 ) and one study was conducted in each of the following countires: Spain (Juan et al, 2006 ), China (Tang et al, 2018 ), Turkey (Clark et al, 2007 ), Canada (Tang et al, 2018 ), Thailand (Tanvejsilp et al, 2017 ), Indonesia (Karuniawati et al, 2019 ), and India (Thomas et al, 2018 ). There were 10 cohort studies (Carter et al, 2017 ; Hess et al, 2009 ; Jakeman et al, 2020 ; Juan et al, 2006 ; Lara-Júnior et al, 2022 ; Lopes et al, 2017 ; Moadebi et al, 2005 ; Tanvejsilp et al, 2017 ; Tavitian et al, 2003 ; Thomas et al, 2018 ), two RCTs (Clark et al, 2007 ; Tang et al, 2018 ) and 1 quasi-experimental study (Karuniawati et al, 2019 ). Six studies had a comparator group (Clark et al, 2007 ; Juan et al, 2006 ; Karuniawati et al, 2019 ; Moadebi et al, 2005 ; Tang et al, 2018 ; Tanvejsilp et al, 2017 ); one study compared pharmacist care to nurse care (Moadebi et al, 2005 ), while three studies compared pharmacist care to usual practice (Clark et al, 2007 ; Hess et al, 2009 ; Tang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-adherence to treatment is a significant factor causing inadequate drug effectiveness and adverse reactions, leading to drug resistance 24 25. Pharmacist intervention through CPS can address these issues,25–28 but its implementation is challenging18 and requires a comprehensive and collaborative approach focusing on the unique traits of each patient 2 7…”
Section: Discussionmentioning
confidence: 99%